Effects of additives additions and sintering techniques on the microstructure and mechanical properties of Zirconia Toughened Alumina (ZTA): A review. (August 2022) - Sktani, Zhwan Dilshad Ibrahim; Arab, Ali; Mohamed, Julie Juliewatty; Ahmad, Zainal Arifin
Abstract: ZTA is an innovative ceramic composite for advanced industrial applications because of its superior mechanical properties compared to both pure Al2 O3 and ZrO2 . Therefore, it was subjected to extensive study since 1970s. The last review by Wang and Stevens (1989) focused on the development of ZTA ceramics through controlling powder preparation and densification processes. The current review verified the effects of adding various additives into ZTA ceramics utilising several sintering techniques and preparation routes to further enhance their mechanical properties through governing their microstructure pattern. It shows that the porosity, number and total quantity of additives, the reaction of additives with ZTA ingredients, grains sizes, and the number of secondary phases are important parameters affecting the mechanical properties of ZTA. This review also reported the most recent progress in the enhancement of mechanical properties of ZTA as an alternative to other costly related advanced materials industries and suggested a few approaches to accomplish this objective. Highlights: Effect of additives addition on the mechanical properties of ZTA is investigated. Influence of the sintering techniques on ZTA mechanical properties is discussed. Impact of additives on the microstructure and new phases' formation is examined. Future developments and potential research challenges are summarised and proposed. Approaches were suggested for ZTA replacement of costly advanced materials.